Involvement of LPA1 receptor signaling in the reorganization of spinal input through Abeta-fibers in mice with partial sciatic nerve injury - Chun Jerold; Matsumoto Misaki; Xie Weijiao; Ueda Hiroshi (SAGE Publishing, 2008)
Abstract Lysophosphatidic acid receptor subtype LPA1 is crucial for the initiation of neuropathic pain and underlying changes, such as up-regulation of Ca2+ channel α2δ-1 subunit in dorsal root ganglia (DRG), up-regulation of PKCγ in the spinal dorsal horn, and demyelination of dorsal root fibers. In the present study, we further examined the involvement of LPA1 signaling in the reorganization of Aβ-fiber-mediated spinal transmission, which is presumed to underlie neuropathic allodynia. Following nerve injury, the phosphorylation of extracellular-signal regulated kinase (pERK) by Aβ-fiber stimulation was observed in the superficial layer of spinal dorsal horn, where nociceptive C- or Aδ-fibers are innervated, but not in sham-operated wild-type mice. However, the pERK signals were largely abolished in LPA1 receptor knock-out (Lpar1-/-) mice, further supported by quantitative analyses of pERK-positive cells. These results suggest that LPA1 receptor-mediated signaling mechanisms also participate in functional cross-talk between Aβ- and C- or Aδ-fibers.